The Investigation of Groundwater Potential by Vertical Electrical Sounding (VES) Approach in Arguni Bay Region, Kaimana Regency, West Papua - Santosa, Langgeng Wahyu; Adji, Tjahyo Nugroho (Universitas Muhammadiyah Surakarta, 2007)
This research was conducted within some villages in the surrounding area that administratively including Arguni Bay District, Kaimana Regency, West Papua. The main objective of this study is to vertically measure resistivity value of aquifer with the intention of recognizing deep groundwater potency as a source of nativeâs domestic needs. In addition, VES method by Schlumberger electrode array was applied within 18 locations, which expectantly represent the whole area of research. The resistivity data is then interpreted by IP2Win 2.1 Geoelectric Software to entirely describe the aquifer system as well as the occurrence of groundwater. The result indicates that vertically, the aquifer system is dominated by interbedded of claystone and sandstone (argillite group) as a past marine environment mineral. In addition, geomorphological and resistivity sounding interpretation gives a viewpoint that the landforms of the research area may be typified as Structural Mountain with the slope direction is towards the island beaches. Also, structurally, the main groundwater system is fractured aquifer with very limited productivity of groundwater resources. As consequences, this aquifer is more to be an aquitard, rather than an aquifer.